Promotion of tree planting on small farms in the area of Acosta-Puriscal, Costa Rica - Beer, John (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), Turrialba (Costa Rica), 2014)
6 ref. Sum. (En, Es)